Reverberation Reduction for Improved Speech Recognition - Tashev, Ivan; Allred, Daniel (Proceedings of Hands-Free Communication and Microphone Arrays, 2005)
In this paper we present a dereverberation algorithm for improving automatic speech recognition (ASR) results with minimal CPU overhead. As the reverberation tail hurts ASR the most, late reverberation is reduced via gain-based spectral subtraction. We use a multi-band decay model with an efficient method to update it in realtime. In reverberant environments the multi-channel version of the proposed algorithm reduces word error rates (WER) up to one half of the way between those of a microphone array only and a close-talk microphone. The four channel implementation requires less than 2% of the CPU power of a modern computer.